UTAUT2 Model in Increasing the Intention to Use Digital Payment of QRIS - Ginsi Trianesti; T. Ezni Balqiah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Digital payment systems, particularly the Quick Response Code Indonesian Standard, are gaining traction in Indonesia, yet adoption among non-users remains limited due to cultural preferences for cash and data security concerns. This study investigates the factors influencing the intention to use the Quick Response Code Indonesian Standard among non-users, employing the Unified Theory of Acceptance and Use of Technology 2 framework, extended with interactivity, intelligence, and convenience. Data were collected from 324 non-users through an online survey distributed via social media platforms and analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that interactivity, intelligence, and convenience significantly enhance performance expectancy, effort expectancy, subjective norms, facilitating conditions, and habit, which in turn drive use intention. Additionally, hedonic motivation, price value, and perceived risk positively influence use intention, with perceived risk’s effect indicating manageable risks. The study concludes that user experience factors are critical for increasing adoption in Indonesia’s cash-dominated economy. However, its focus on non-users limits generalizability. Future research should explore active users and cultural factors to deepen understanding of digital payment adoption.